Effect of sulphur on yield, uptake of nutrients and economics of garlic (Allium sativum), onion (Allium cepa) and potato (Solanum tuberosum) in alluvial soil - SINGH, DINESH PRATAP; SEEMA; ALI, JAVED; SINGH, S P; SINGH, VINAY (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted during winter (Rabi) season 2009-2011 to study the effect of sulphur fertilization on garlic (Allium sativum L.), potato (Solanum tuberosum L.) and onion (Allium cepa L.) on alluvial soil at Bichpuri, Agra (Uttar Pardesh) . The treatments comprised five levels of S (0, 15, 30, 45 and 60 kg/ha) were evaluated in randomized block design with four replications. The results revealed that the application of sulphur up to 45 kg/ha significantly increased the yields and dry matter production of vegetable crops, whereas, at higher sulphur level (60 kg/ha) the yield tended to decrease in potato. The magnitude of mean response to sulphur application differed from crop to crop and were recorded as onion (30.2 %) > garlic (22.5 %) > potato (17.0 %) over control. Sulphur application progressively increased the uptake of S in vegetable crops. A phenomenal increase in N, P and K uptake, except of Zn, was recorded in vegetable crops due to increasing levels of S up to 60 kg/ha. The maximum removal of N, P and K was recorded with potato tubers while those of S and Zn with onion bulbs. The higher amounts of protein and protein yield were recorded in potato followed by onion and garlic. Sulphur application significantly improved the content and yield of protein in these vegetable crops over control and maximum values were recorded at 60 kg S/ ha. Garlic and onion gave maximum net returns and B:C ratio with 60 kg S/ha and potato at 45 kg/ha. The apparent recovery of sulphur was influenced by S levels with maximum at 45 kg S/ha, except potato where maximum (36.3 %)apparent recovery was recorded with 15 kg S/ha. Better sulphur use efficiency in garlic, onion and potato was obtained with 30 kg S/ha. The sulphur use efficiency decreased with its increasing levels and minimum use efficiency was recorded with 60 kg S/ha application.